COMPARATIVE ANALYSIS OF SOME TECHNIQUES IN THE BIOLOGICAL RECLAMATION OF CRUDE OIL POLLUTED AGRICULTURAL SOILS IN NIGERIA (Nigerian Journal of Technology, 2006)
Replicate field cells involving some techniques aimed at enhancing the bioremediation of crude oil polluted agricultural soils were used in a comparative study to determine the factors and environmental conditions that could optimize the bioremediation process on crude oil polluted soils in Nigeria. The treatment techniques involved the application of different levels of: nutrient, water, oxygen exposure, and the combined effect of different levels of oxygen, water and nutrient. These formed four options, A, B, C and D. Options E and F were Phytoremediation (using corn and elephant grass) and Biopile treatments respectively. The experiments involved the simulation of conditions of a major spill by pouring crude oil on the cells from perforated cans and the in-situ bioremediation of the polluted soils using the techniques that consisted in the manipulation of different variables within the soil environment. The analysis of soil characteristics after a six-week remediation period indicated that the total heterotrophic bacterial counts increased in all treatment options while the organic carbon and total hydrocarbon content (THC) of the soils decreased with time across the various options. Option C (involving different levels of oxygen exposure) produced the highest hydrocarbon loss of 94% while Option E (phytoremediation using corn and grass) recorded the lowest level of hydrocarbon loss (51%). The THC losses recorded in the other options, which involved different levels of: nutrient application, water application; the combined effect of varying oxygen, water and nutrients and the use of biopiles ranged from 67% to 91%. Option A (the application of different levels of nutrients) had a hydrocarbon loss of 78%, Option B (involving different levels of water application) recorded a 67% hydrocarbon loss, the combined effect of different levels of oxygen, water and nutrients (Option D) recorded a hydrocarbon loss of 91% while the use of biopiles (Option E) had a hydrocarbon loss of 51%. These results were quite different from the control site which had an increased THC level (14 316 - 14 580 mg kg-1) during the study period. The results of the study revealed that different levels of oxygen exposure, water and nutrient application induced different biodegradation rates with the implication that an accelerated bioremediation with the best biodegradation rates could be achieved when polluted soils are remedied with techniques that maintain optimum levels of these factors.